Toll‐like receptor 4 ablation rescues against paraquat‐triggered myocardial dysfunction: Role of ER stress and apoptosis. Issue 2 (21st July 2016) - Lei, Yonghong; Li, Xue; Yuan, Fang; Liu, Lu; Zhang, Juan; Yang, Yanping; Zhao, Jieqiong; Han, Yan; Ren, Jun; Fu, Xiaobing
ABSTRACT: Paraquat is a nitrogen herbicide imposing severe organ toxicity in human leading to acute lung injury and heart failure. The present study was designed to examine the impact of ablation of the innate proinflammatory mediator toll‐like receptor 4 (TLR4) in paraquat‐induced cardiac contractile dysfunction and the underlying mechanisms involved with a focus on endoplasmic reticulum (ER) stress and apoptosis. Adult male wild‐type (WT) and TLR4 knockout (TLR4 −/− ) mice were challenged with paraquat (45 mg/kg, i.p.) for 48 h prior to the assessment of myocardial and cardiomyocyte sarcomere function, ER stress, apoptosis and inflammation. Acute paraquat challenge exerted myocardial functional and geometric alterations including enlarged left ventricular end systolic diameter (LVESD), reduced fractional shortening, decreased sarcomere shortening, maximal velocities of sarcomere shortening and relengthening associated with unchanged LV posterior wall thickness, septal thickness, LV end diastolic diameter (LVEDD), heart rate, sarcomere length, time‐to‐peak shortening and time‐to‐90% relengthening. Although TLR4 ablation did not affect mechanical properties in the heart, it significantly attenuated or ablated paraquat‐induced cardiac contractile anomalies. Moreover, paraquat imposed overt ER stress, apoptosis and inflammation as evidenced by upregulation of Bip, CHOP, Caspase‐3, −9, Bax, Bad, and IL‐1β, phosphorylation of PERK, eIF2α and IΚB, as well as activation of the stress molecules ERK and p38, with unchanged Caspase‐8, Bcl2, TNF‐α, p53, HMGB1, MyD88 and phosphorylation of Akt, GSK3β and JNK, the effects of which were attenuated or negated by TLR4 knockout. Taken together, our results suggested that TLR4 ablation alleviated paraquat‐induced myocardial contractile dysfunction possibly through attenuation of ER stress, apoptosis and inflammation. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 656–668, 2017.